Real Options and Product Life Cycles - Bollen, Nicolas P. B. (Management Science, 1999)
In this paper, I develop an option valuation framework that explicitly incorporates a product life cycle. I then use the framework to value the real option to change a project's capacity. Standard techniques for valuing real options typically ignore product life cycle models and specify instead a constant expected growth rate for demand or price. I show that this specification can lead to significant error in the valuation of capacity options. In particular, the standard technique tends to undervalue the option to contract capacity and overvalue the option to expand capacity. This result has important implications for capital investment decisions, especially in high-technology industries that feature regular introductions of newly improved products.